3 Dimensional Thermal Mapping - Altuntas, Nihal; Cakmak, Furkan; Uslu, Erkan; Balcilar, Muhammet; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2016)
3 dimensional RGB map extraction with use of registered RGB and depth data from Kinect has been widely implemented. This wide usage mostly comes from the fact that intrinsic and extrinsic parameters for both RGB and the infrared cameras are known out of the shelf. This study mostly focuses on 3 dimensional thermal mapping with RGBD-SLAM (RGBD Simultaneous Localization And Mapping) method utilizing the calibration and registration of a thermal camera with Kinect infrared camera.
Keywords: kinect; thermal camera; infrared camera; calibration; RGBD-SLAM; 3D thermal mapping; Engineering